INFORMATION ASYMMETRY AND HERDING BEHAVIOR - Komalasari, Puput Tri (UI Scholars Hub, 2016)
Conceptually, the stock market is strong form efficient in the long term. However, in practice, there are various forms of market anomalies that undermine the accuracy of the efficient market hypothesis. One factor suspected as the cause of market inefficiency is herding behavior. Investors herd when they imitate the actions of other investors. This behavior occurs when there is a continuous interaction among rational investors that prevents them from seeking information about market fundamentals. This study provides new insights by including information asymmetry as a moderating variable. This research examines the phenomenon of herding behavior in the Indonesia Stock Exchange as well as examines directly the effect of information asymmetry on herding behavior. The period of study is 2008 using time series of daily stocks data that actively traded in the capital market. Results of this study find that investor tends to follow market consensus when price changes at the low level, but when there is large price swing market participant acts independently from other investors. Interestingly, this study finds that information asymmetry is a necessary condition for the existence of herding behavior.